Explorative survey on the usage and needs of Mobile Health Applications (mhealth) amongst caregivers in taking care of stroke survivors - Firdaus A.; Noor Azah Abd Aziz; Wan Asyraf Wan Zaidi; Fairuz A. (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Mobile health (mHealth) applications may assist stroke caregivers in answering the unmet needs of inadequate information and support from healthcare professionals. This study aimed to explore the usage and needs of mHealth applications among stroke caregivers and its associated factors. This cross-sectional study involved 207 stroke caregivers attending hospital and community-based stroke clinics in Kuala Lumpur between December 2020 until March 2021. The survey was done through newly developed self-administered bilingual questionnaires using face to face interviews, telephone interviews and Google form. Most caregivers (77.8%) used at least one mHealth application for self-care or during the caregiving process. The three most types of mHealth applications were contacting healthcare professionals (89.9%), disease monitoring (89.4%) and health information (89.4%). The three most features of mHealth applications were free to download/use (94.7%), simple interface (93.7%) and data security/privacy (93.7%). Chi-square test of association showed managing appointment (χ2 (1) = 5.65, p = 0.017), health information (χ2 (1) = 6.72, p = 0.01), disease monitoring (χ2 (1) = 9.58, p = 0.002), contacting healthcare professional (χ2 (1) = 6.27, p = 0.012) and patient disability level (χ2 (1) = 4.29, p = 0.038) were significantly associated with specific types of mHealth applications. In conclusion, the overall usage of mHealth applications among stroke caregivers was high, with the need of specific types and features in mHealth applications among stroke caregivers.